(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In today’s globalization environment, the demands placed on the education system are becoming increasingly complex. Society needs individuals who can think independently, communicate, and constantly develop their knowledge. Therefore, the education system is faced with the task of not only imparting knowledge, but also of engaging students in learning and forming their internal motivation. The problem of passive learners remains particularly relevant in the teaching of the native language in secondary schools.